To Compare the Effect of Single Antioxidant Versus Combined Antioxidants in Patients with Elevated Reactive Oxygen Species Levels - Mir Abid Jan, Khalil Ur Rehman, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Reactive oxygen species (ROS) play an important role in the pathophysiology of various chronic diseases by inducing oxidative stress, cellular damage, and inflammation. Antioxidant supplementation is commonly used to mitigate these effects, but limited evidence exists comparing the efficacy of single versus combined antioxidant therapies in patients with elevated ROS levels. Objective: To compare the effect of single antioxidant supplementation versus combined antioxidant therapy on ROS levels in patients with high oxidative stress. Methodology: This comparative interventional investigation was carried out from March to September 2023 at the Institute of Kidney Diseases, MTI Hayatabad, Peshawar. 110 patients with high ROS levels were recruited and split into two groups at random. For eight weeks, Group B received a combination of antioxidants (Vitamin C 500 mg + Vitamin E 400 IU daily), while Group A received just one antioxidant (Vitamin C 500 mg daily). ROS levels were assessed both before and after the intervention. SPSS version 26 was used for statistical analysis. Independent and paired t-tests were used; a significance level of p < 0.05 was used. Results: Both groups showed significant reductions in ROS levels post-intervention (Group A: -3.6 µmol/L; Group B: -6.0 µmol/L, p < 0.001). However, the between-group difference in mean ROS reduction was not statistically significant (p = 0.661). Conclusion: Both single and combined antioxidant therapies significantly reduced ROS levels in patients with elevated oxidative stress. Although combined therapy showed a greater numerical reduction, the difference was not statistically significant. Keywords: Reactive oxygen species, antioxidants, vitamin C, vitamin E, oxidative stress, combination therapy.